A novel mutation of walK confers vancomycin-intermediate resistance in methicillin-susceptible Staphylococcus aureus - Jiade Zhu; Banghui Liu; Xueqin Shu; Baolin Sun (Elsevier, 2021)
With the treatment failure by vancomycin and poor clinical outcomes, the emergence and spread of vancomycin intermediate-resistant Staphylococcus aureus (VISA) has raised more concerns in recent years. While most VISA strains are isolated from methicillin-resistant S. aureus (MRSA), the mechanism underlying the generation of VISA from methicillin-susceptible S. aureus (MSSA) is still largely unknown. Here, we identified a total of 10 mutations in 9 genes through comparative genome analysis from laboratory-derived VISA strain. We verified the role of a novel mutation of WalK (I237T) and our results further indicated that the introduction of WalK (I237T) by allelic replacement can confer vancomycin resistance in MSSA with common VISA characteristics, including thickened cell walls, reduced autolysis, and attenuated virulence. Consistent with these phenotypes, real-time quantitative reverse transcription-PCR revealed the altered expression of several genes associated with cell wall metabolism and virulence control. In addition, electrophoretic mobility shift assay indicated that WalR can directly bind to the promoter regions of oatA, sle1, and mgt, fluorescence-based promoter activity and β-galactosidase assays revealed WalK (I237T) can alter promoter activities of oatA, mgt, and sle1, thus regulating genes expression. These findings broaden our understanding of the regulatory network by WalKR system and decipher the molecular mechanisms of developmental VISA resistance in MSSA with point mutations.